Hubungan Penguasaan Kosakata dengan Kemampuan Menulis Narasi Siswa Kelas VII SLBN Dr. Radjiman Wedyodiningrat Ngawi - Suratmi; Dwi Rohman Soleh; Panji Kuncoro Hadi (Tamilis Synex: Multidimensional Collaboration, 2025)
This research is correlational in nature. The objective of this study is to determine whether there is a positive and significant relationship between vocabulary mastery in Indonesian and the narrative writing ability of visually impaired students in grade VII at SLBN Dr. Radjiman Wedyodiningrat Ngawi. The sample of this study consists of 5 visually impaired students in grade VII. Data collection techniques were conducted through vocabulary tests and narrative writing tasks. The collected data were analyzed quantitatively using correlation analysis methods. The quantitative results show that 1) The correlation analysis results reveal that the score from vocabulary tests conducted by the researcher on visually impaired grade VII students yielded a value of 0.998, which is greater than the product-moment correlation table value of 0.878. This indicates that the calculated r-value is greater than the r-table value (0.998 > 0.878). Based on these findings, it can be concluded that there is a relationship between vocabulary mastery and narrative writing ability among visually impaired grade VII students at SLBN Dr. Radjiman Wedyodiningrat Ngawi.